Publishing and the scientific journals at the 2.0 crossroads - Torres-Salinas, Daniel (Anuario ThinkEPI, 2009)
The status of scientific publication in relation to web 2.0 and its opportunities is reported. First, we discuss how scientific journals have always been working under a paradigm and web 2.0 is only a step in the electronic paradigm. Then we introduce the concept of impostor 2.0 to explain that the scientific community in this new scenario is only affected by technological changes, not social ones, because many of the values of web 2.0 are part of the scientific ethos. In conclusion, we present some examples of editorial policies clearly directed to the social web that are setting the path to scientific publishing.